2002
DOI: 10.1007/3-540-45649-x_6
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Quantum Magnets

Abstract: A description of different phases of two dimensional magnetic insulators is given.The first chapters are devoted to the understanding of the symmetry breaking mechanism in the semi-classical Néel phases. Order by disorder selection is illustrated. All these phases break SU (2) symmetry and are gapless phases with ∆S z = 1 magnon excitations.Different gapful quantum phases exist in two dimensions: the Valence Bond Crystal phases (VBC) which have long range order in local S=0 objects (either dimers in the usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
140
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 192 publications
(478 reference statements)
3
140
0
Order By: Relevance
“…The minimum in dM/dB is due to the fact that for low temperatures when B ≈ Bsat/3 there exist two competing families of spin configurations of which one behaves magnetically "stiff" leading to a reduction of the differential susceptibility. The magnetism of frustrated one-, two-, and threedimensional lattice spin systems is a fascinating subject due to the richness of phenomena that are observed [1,2,3]. In this Letter we report that one effect of geometrical frustration, which so far has been reported [4] only for the theoretical model of classical spins on a Kagomé lattice, already appears for a class of zero-dimensional materials, namely certain magnetic molecules hosting highly symmetric arrays of classical or quantum spins.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…The minimum in dM/dB is due to the fact that for low temperatures when B ≈ Bsat/3 there exist two competing families of spin configurations of which one behaves magnetically "stiff" leading to a reduction of the differential susceptibility. The magnetism of frustrated one-, two-, and threedimensional lattice spin systems is a fascinating subject due to the richness of phenomena that are observed [1,2,3]. In this Letter we report that one effect of geometrical frustration, which so far has been reported [4] only for the theoretical model of classical spins on a Kagomé lattice, already appears for a class of zero-dimensional materials, namely certain magnetic molecules hosting highly symmetric arrays of classical or quantum spins.…”
mentioning
confidence: 77%
“…In the quantum formula the multiplicity factor corresponds to the classical geometrical function G(S). Each of these quantities has two distinct branches, depending on whether n is in the interval [0, s] or [s + 1, 3s] or whether S is in the interval [0, 1] or [1,3]. In fact, the existence of two distinct branches becomes manifest in various higher derivatives of Z(t, b) at nonzero temperatures for fields in the vicinity of B = B sat /3.…”
Section: K (See Insetmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of unpaired but nevertheless strongly interacting spins gives rise to a macroscopically degenerate ground state manifold, with increasingly glassy dynamics as x is lowered. Physical realisations of the S = 1/2 kagomé Heisenberg antiferromagnet have been long sought after because it is expected that the ground state of this system can retain the full symmetry of the underlying effective magnetic Hamiltonian [1,2]; the geometry of the kagomé lattice frustrates the classical Néel antiferromagnetic ordering, and no symmetry-breaking transition is expected even at T = 0 [3,4,5,6,7]. It has been suggested that even in the thermodynamic limit the symmetric quantum-mechanical electronic ground state is protected from quantum-mechanical dissipation [8] by a gap between the non-magnetic ground state and the lowest magnetic (triplet) excitations [9,10].…”
mentioning
confidence: 99%